Teaching Econometrics Dynamically with R-Shiny. - Metzger, Shawna K. (PS: Political Science & Politics, 2022)
The article presents the discussion on allocating the time giving to students the best chance of learning the content. Topics include discussing regression models by providing students with the ability for interacting dynamically with the material; and Shiny apps accepting user input through sliders, radio buttons, checkboxes, dropdowns, text input, and toggle buttons.